EFFECT OF ADDING ANNATTO (Bixa orellana) SEEDS EXTRACT AND TOCOTRIENOL TO SEMEN EXTENDER ON CRYOPRESERVED SEMEN OF HOLSTEIN BULLS - Rehan, M. M. A.; Banana, H. J. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study was conducted to investigate the effect of adding various concentrations of annatto alcoholic extract  of (Bixa orellana) and tocotrienol on characteristics of cryopreserved semen of Holstein bulls. Collected semen were pooled and diluted with tris egg yolk extender, then equally divided into five groups as following: Control group (C) with tris extender only, T1 contain 150 mg annatto seed extract/ 25 ml extender, T2 contain 200 mg annatto seed extract / 25 ml extender, T3 contain 3 Mm tocotreinol /25 ml extender and T4 contain 4 Mm tocotreinol/25 ml extender. All groups were subjected to a cryopreservation protocol. The parameters of semen assessment including: Motility, viability, abnormality, plasma membrane and acrosome integrity, malondialdehyde (MDA), total antioxidant capacity (TAC) and DNA fragmentation Index (DFI). All the previous parameters were done for both cooled and frozen semen after 48 hrs, 3 and 6 months. The results showed that there were a significant differences (p≤0.05) among the treatments in the percentage of sperm motility, viability, plasma membrane and acrosome integrity compared with the control group, also there were significant differences in  sperm total abnormalities, MDA, TAC concentrations and DFI percentage among all the treatments after all  cryopreservative periods compared with the control group..